2007
DOI: 10.1556/avet.55.2007.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting and refeeding on the antioxidant system in cockerels and pullets

Abstract: The effect of fasting and refeeding on total antioxidant status (TAS), glutathione peroxidase (GSH-Px) activity and concentration of some non-enzymatic antioxidant compounds was studied in cockerels and pullets. Blood was collected before and after 48-h fasting and 24 h after refeeding. In cockerels, fasting resulted in a significant decrease of TAS and uric acid concentration. After refeeding, the concentration of TAS remained significantly lower as compared to the control level. At the same time, blood plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The reduction in catalase activity observed in fasted penguins indeed indicates a reduction in the need for antioxidant protection, thus supporting this interpretation. This is reinforced by a previous study which reported that 48-h fasting considerably reduces the antioxidant defenses in the blood of cockerels and pullets (41).…”
Section: R96mentioning
confidence: 65%
“…The reduction in catalase activity observed in fasted penguins indeed indicates a reduction in the need for antioxidant protection, thus supporting this interpretation. This is reinforced by a previous study which reported that 48-h fasting considerably reduces the antioxidant defenses in the blood of cockerels and pullets (41).…”
Section: R96mentioning
confidence: 65%
“…These birds experience five or six long fasting periods during each breeding season, which could increase oxidative stress and, possibly, reduce their fitness. Recent studies on birds suggest that fasting has a negative impact on the oxidative state (Milinkovic‐Tur et al. 2007; Rey et al.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, analyses of the other antioxidative parameters in the blood of the turkeys (FRAP, vitamin C, GSSG+GSH, H 2 O 2 ) demonstrated an initial increase until the 12th week of life, followed by a decrease in the 15th week. Investigations carried out with poultry, laboratory animals and humans have demonstrated that the activity of the antioxidative system, to some extent, is determined by age (Wang et al, 1998;Wickens, 2001;Milinković-Tur et al, 2007;Milinković-Tur et al, 2009). It has been proven that reactive oxygen species that induce cell damage and severe depletion of antioxidative defence elements accumulate in the course of body ageing (Sohal, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…According to observations made in experiments with poultry and humans, the reducing level of FRAP along with age is an effect of depletion of non-enzymatic antioxidants, which are FRAP constituents (glutathione in particular) (Ibrahim et al, 2000;Milinković-Tur et al, 2007;Milinković-Tur et al, 2009). Results in the present study, viz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation